The Mevalonate Pathway Is Important for Growth, Spore Production, and the Virulence of Phytophthora sojae - Yang, Xinyu; Jiang, Xue; Yan, Weiqi; Huang, Qifeng; Sun, Huiying; Zhang, Xin; Zhang, Zhichao; Ye, Wenwu; Wu, Yuanhua; Govers, Francine; Liang, Yue (Frontiers in Microbiology, 2021)
The mevalonate (MVA) pathway in eukaryotic organisms produces isoprenoids, sterols, ubiquinone and dolichols. These molecules are vital for diverse cellular functions, ranging from signaling to membrane integrity, and from post translational modification to energy homeostasis. However, information on the MVA pathway in Phytophthora species is limited. In this study, we identified the MVA pathway genes and reconstructed the complete pathway in Phytophthora sojae in silico. We characterized the function of the MVA pathway of P. sojae by treatment with enzyme inhibitor lovastatin, deletion of the geranylgeranyl diphosphate synthase gene (PsBTS1), and transcriptome profiling analysis. The MVA pathway is ubiquitously conserved in Phytophthora species. Under lovastatin treatment, mycelial growth, spore production, and virulence of P. sojae were inhibited but the zoospore encystment rate increased. Heterozygous mutants of PsBTS1 showed slow growth, abnormal colony characteristics and mycelial morphology. Mutants showed decreased numbers of sporangia and oospores as well as reduced virulence. RNA sequencing analysis identified the essential genes in sporangia formation were influenced by the enzyme inhibitor lovastatin. Our findings elucidate the role of the MVA pathway in P. sojae and provide new insights into the molecular mechanisms underlying the development, reproduction, and virulence of P. sojae and possibly other oomycetes. Our results also provide potential chemical targets for management of plant Phytophthora diseases.